Superior Outcomes With Continuing Tenofovir Versus Switching to Zidovudine in Second-Line Antiretroviral Therapy in Haiti. (23rd November 2021) - Pierre, Samuel; Bocharova, Iryna; Nguyen, Catherine; Homeus, Fabienne; Julmiste, Gaetane; Macius, Youry; Rouzier, Vanessa; Severe, Patrice; Marcelle Deschamps, Marie; Moise, Colette Guiteau; Bellot, Clovy; Wu, Johnny; et al.
Abstract: We compared viral suppression rates between patients who continued tenofovir disoproxil fumarate (TDF)/lamivudine (3TC) vs switched to zidovudine (ZDV)/3TC in combination with a boosted protease inhibitor after failure of first-line efavirenz/TDF/3TC. We found higher rates of viral suppression with continued TDF/3TC compared with switching to ZDV/3TC.